A Review on Identification Methods of Road Friction Coefficient - Qi, Gengxin; Fan, Xiaobin; Li, Hao (Recent Patents on Engineering, 2022)
Background: The development of the tire/road friction coefficient measurement and estimation system has far-reaching significance for the active electronic control safety system of automobiles and is one of the core technologies for autonomous driving in the future. Objective: Estimating the road friction coefficient accurately and in real-time has become prominent in research. Researchers have used different tools and proposed different algorithms and patents. These methods are widely used to estimate the road friction coefficient or other related parameters. This paper gives a comprehensive description of the research status in the field of road friction coefficient estimation. Method: According to the current research status of Chinese and foreign scholars in the field of road friction coefficient recognition, the recognition methods are mainly divided into two categories: cause-based and effect-based. Results: This literature review will discuss the existing two types of identification methods (causebased and effect-based) and analyze the applicable characteristics of each algorithm. Conclusion: The two recognition methods are analyzed synthetically, and the development direction of road friction coefficient recognition technology is discussed.
Keywords: cause-based